Serum phosphorus is related to left ventricular remodeling independent of renal function in hospitalized patients with chronic kidney disease. (15th October 2016) - Zou, Jun; Yu, Yi; Wu, Ping; Lin, Fu-Jun; Yao, Yao; Xie, Yun; Jiang, Geng-Ru
Abstract: Background: Increasing evidence indicated that phosphorus emerged as an important cardiovascular risk factor in patients with chronic kidney disease (CKD). The fact that serum phosphorus was closely linked to vascular and valvar calcification may account for one important reason. However, left ventricular remodeling may also serve as another potential mechanism of the cardiac toxicity of phosphorus. In the present study, we evaluated the association of serum phosphorus with left ventricular remodeling. Methods: We investigated consecutive hospitalized patients with pre-dialysis CKD, who did not have symptomatic heart failure or take any phosphorus binder or calcitriol medications. Transthoracic echocardiography was applied to assess their left ventricular remodeling indices, both structural and functional. Results: The 296 study subjects (mean age 56.4 years) included 169 (57.1%) men, 203 (68.6%) hypertensive patients. In addition to gender, systolic blood pressure, and estimated glomerular filtration rate, serum phosphorus was an independent determinant of left ventricular mass index (LVMI, P  = 0.001). Similarly, serum phosphorus was also a determinant of left ventricular end diastolic dimension ( P  = 0.0003), but not of relative wall thickness. In multivariate logistic analyses, serum phosphorus was significantly and independently associated with the prevalence of left ventricular hypertrophy (LVH, odds ratio [OR] 2.38 for each 1 mmol/L increase, 95% CI 1.20–4.75, P  = 0.01). Moreover, the association was only confirmatory in eccentric LVH (OR 3.01, 95% CI 1.43–6.32, P  = 0.003) but not in concentric LVH (1.38, 95% CI, 0.54–3.49, P  = 0.50). Conclusion: Serum phosphorus was significantly and independently associated with LVMI and the prevalence of eccentric LVH in hospitalized patients with CKD.